(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the historical conditions under which Amir Timur (Tamerlane) consolidated political power in Movarounnahr (Transoxiana) in the second half of the fourteenth century, and the impact of this process on the region’s socio-cultural development. Against the background of the fragmentation of the Chagatai ulus and the campaigns of the Mogul khans, it traces Timur’s rise, his struggle with Amir Husayn, his attainment of independent rule, and his patronage of cities, trade, and crafts.